Low-Cost Solution-Processed MoS2Quantum Dots-Based Deep UV Photodetector for Monitoring Disinfection - Gupta P.K.; Pandey U.; Pal B.N.; Pandey A. (My University, 2025)
Deep UV radiation is commonly used as a disinfectant with an appropriate dose for better efficacy. However, continuous monitoring of UV radiation is required to have appropriate dose exposure for proper disinfection. This article reports a low-cost solution-processed fabrication method of the UV photodetector (PD) with a device geometry of Al/MoS2 quantum dots (QDs)/Al on Si/SiO2 substrate, which is sensitive to deep UV radiations 275 nm, commonly used for water and surfaces disinfection technologies. Colloidal MoS2 QDs with an average size of 1.99 nm have been synthesized by an inexpensive hydrothermal method. The surface ligand of MoS2 QDs has been replaced by a shorter ligand 1, 2-ethanedithiol (EDT) to reduce dot-to-dot distance. The fabricated device shows high responsivity (21.62 mA/W), external quantum efficiency (EQE) (9.74%), and detectivity (3.57× 1010 Jones) under the deep UV irradiation of 275 nm. The PD has a good photoresponse speed of rise and decay times of 173 and 92 ms, respectively. © 1963-2012 IEEE.